PEMANFAATAN TANAMAN PETUNIA UNGU (Ruellia simplex C.) SEBAGAI PENYERAP LOGAM TIMBAL (Pb) PADA MEDIA TUMBUH TANAH - Mutia Wulandari; Alimuddin -; Bohari Yusuf (JURNAL KIMIA MULAWARMAN, 2013)
Has been done a research concerning the use of Petunia Ungu (Ruellia simplex C.) plants as an absorbent lead metal (Pb) in the soil growing medium. The research almed to determine the levels of lead metal in petunia ungu plants and determine the effect of variations of concentrations also to determine the effect of absorption time in plants during planting petunia ungu 1, 2, 3 and 4 weeks then petunia ungu planted in the soil as the growing that was added a solutions of lead respectively 0, 25, 50, 75 and 100 mg/L. A soil sample preparation was conducted by wet digestion method and petunia ungu plants by dry digestion method. Metal levels of lead in the soil samples and petunia ungu plants was measured by atomic absorption spectrophotometer at wavelengths of 283,3 nm. The result of research showed that petunia ungu plants can absorb lead metal, the average levels of lead metal in petunia ungu plants consist of 0 ppm 1, 2, 3 and weeks 1,2303; 1,3190; 1,5064 and 1,6915 mg/Kg. 25 ppm 2,1779; 3,0426; 3,4145 and 3,3643 mg/Kg. 50 ppm 3,1317; 3,4316; 3,8689 and 4,2841 mg/Kg. 75 ppm 3,1179; 4,6695; 6,5676 and 6,6828 mg/Kg. 100 ppm 2,5205; 3,6302; 5,4442 and 6,9167 mg/Kg. beside that a lead metal content in the soil as a growing medium decreased.